ANALISIS KUALITAS LAYANAN PEMESANAN TIKET ONLINE TAMAN HIBURAN MENGGUNAKAN METODE SERVQUAL STUDI KASUS: (TRANS STUDIO, DUFAN, TMII) - Feby Putri Herdiana; Titin Kristiana (Universitas Putera Batam, 2026)
The advancement of digital technology has driven many amusement parks to offer online ticket booking services. However, the quality of these services still raises concerns, such as unfriendly user interfaces, delayed payment confirmations, and slow customer service responses. This study aims to analyze the quality of online ticket booking services at three major amusement parks—Trans Studio, Dunia Fantasi (Dufan), and Taman Mini Indonesia Indah (TMII)—and measure the gap between user expectations and perceptions using the SERVQUAL method. This quantitative research involved distributing questionnaires to 390 respondents. The research instrument is based on five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results reveal that all three amusement parks showed negative gap scores, indicating that the services did not meet user expectations. TMII recorded the highest average gap of - 0.44, while Trans Studio had the smallest gap of -0.27, making it the park with the best perceived service quality. Assurance and Reliability were identified as the most problematic dimensions. This study contributes by helping amusement park managers evaluate and improve their digital service systems to better meet customer expectations.